2004
DOI: 10.1074/jbc.m313657200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Organization and Properties of Annexin 2-Membrane Complexes

Abstract: Annexin 2 belongs to the annexin family of proteins that bind to phospholipid membranes in a Ca 2؉ -dependent manner. Here we show that, under mild acidic conditions, annexin 2 binds to and aggregates membranes containing anionic phospholipids, a fact that questions the mechanism of its interaction with membranes via Ca 2؉ bridges only. The H ؉ sensitivity of annexin 2-mediated aggregation is modulated by lipid composition (i.e. cholesterol content). Cryo-electron microscopy of aggregated liposomes revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 65 publications
(104 reference statements)
4
43
0
Order By: Relevance
“…At mild acidic pH, AIIt undergoes conformational changes similar to those induced by Ca 2 þ . Thus, ANX II appears to have access to the hydrophobic part of the cellular membranes at both acidic pH in the absence of Ca 2 þ and at neutral pH in the presence of Ca 2 þ (Lambert et al, 2004). This may explain our findings of a significant increase in the crosslinking of gastrins to ANX II (B32-36 kDa) at slightly acidic pH (Figure 3b).…”
Section: Identification Of Proteins In Band C By Seldi-tof-ms and Malmentioning
confidence: 59%
“…At mild acidic pH, AIIt undergoes conformational changes similar to those induced by Ca 2 þ . Thus, ANX II appears to have access to the hydrophobic part of the cellular membranes at both acidic pH in the absence of Ca 2 þ and at neutral pH in the presence of Ca 2 þ (Lambert et al, 2004). This may explain our findings of a significant increase in the crosslinking of gastrins to ANX II (B32-36 kDa) at slightly acidic pH (Figure 3b).…”
Section: Identification Of Proteins In Band C By Seldi-tof-ms and Malmentioning
confidence: 59%
“…This could allow them to organize the interface between the cytoplasm (or cytoskeleton) and the cytoplasmic face of cellular membranes. In fact, cryoelectron and atomic force microscopy of annexins bound to model membranes have provided compelling images of the proteins forming two-dimensional lattices or certain domains on the surface of membranes (Janshoff et al, 2001;Lambert et al, 1997;Reviakine et al, 2000;Lambert et al, 2004). Although the coating of target membranes to establish and/or regulate lateral membrane domains is likely to be a key element of annexin function, a few questions remain.…”
Section: Annexins As Membrane Scaffold Proteinsmentioning
confidence: 99%
“…AnxA2 is a soluble protein predominantly distributed in the cytosol of the cells at resting Ca 2ϩ levels and translocated to cellular membranes under elevated concentrations of intracellular Ca 2ϩ (3). In vitro studies using artificial membranes have shown that AnxA2 preferentially binds to the acidic phospholipids, which are enriched in the cytoplasmic leaflet of cellular membranes (4).…”
Section: Anxa2mentioning
confidence: 99%